Parental Criteria in Book Selection for Preschool Children: A Qualitative Exploration - Küçükkebabcı, Hazal; Özel, Özge (Southeast Asia Early Childhood Journal, 2026)
As books play an increasingly important role in all areas of children’s development, parents’ criteria for selecting books have become an issue that warrants careful examination in terms of their potential to positively influence developmental outcomes. Accordingly, parental book selection practices have gained prominence as a significant research focus. However, despite this growing importance, there remains a limited number of qualitative studies that explore parents’ book selection criteria during the preschool period. Therefore, the purpose of this study was to examine the criteria parents consider when selecting books for their children. The study employed a basic qualitative research design, and data were collected through semi-structured interviews with 127 parents of children aged 0–6 years, who were recruited using the snowball sampling method. The collected data were analyzed using content analysis. The findings revealed that parents primarily attend to content appropriateness, age suitability, and visual characteristics when selecting books for their children. In contrast, relatively limited attention was given to criteria such as moral values, customs and traditions, relevance to real life, privacy, price, and publishing houses. These results indicate that parents tend to prioritize educational content, developmental appropriateness, and visual appeal, while placing less emphasis on economic, cultural, and ethical considerations. Although parents also consider aesthetic qualities and individual factors such as whether a book aligns with their child’s interests, the comparatively limited focus on issues such as morality, privacy, cultural relevance, and real-life applicability suggests that a predominantly content-centered approach guides parents’ book selection processes. Overall, while parents favor books that are educational and visually engaging, certain critical dimensions related to ethical, cultural, and contextual suitability may be overlooked.